The activity of galanga (Alpinia galanga) rhizome extract against the growth of filamentous fungi Aspergillus spp. that produce aflatoxin and Fusarium moniliforme - NOOR SOESANTI HANDAJANI; TJAHJADI PURWOKO (Society for Indonesian Biodiversity, 2008)
Galanga (Alpinia galanga L.) rhizome was known to inhibit the growth of pathogenic fungi. The antifungal substances of galangal rhizome were found from their volatile oil. The objectives of this experiment were to study the ethanol extract of galangal rhizome against the growth of filamentous fungi Fusarium moniliforme, Aspergillus flavus, Aspergillus terreus, and Aspergillus niger that produce mycotoxin, especially aflatoxin, based on biomass and colony area and to determinate minimum growth inhibitory concentration the extract of galangal rhizome. The extract of galangal rhizome was significant (p<0.05) effective against biomass of F. moniliforme and A. flavus. The extract of galangal rhizome however was significant (p<0.05) effective against colony area of F. moniliforme, A. flavus and A. niger. The minimum growthinhibitory concentration of extracts galangal rhizome against the growth of A. flavus, F. moniliforme and A. niger were 816, 1,682, and 3,366 mg/L repectively.Â© 2008 Jurusan Biologi FMIPA UNS SurakartaKey words: Aspergillus spp., Fusarium moniliforme, galangal rhizome extract, minimum growth inhibitory concentration